Economic challenges and opportunities in climate change: The case of Africa - Aminu Abdulrahim Olayinka; Baaba Sule; Emmanuel John Kaka (Studies in Economy and Public Policy, 2025)
Purpose: This study aims to identify the causes and consequences of CC and some important economic potentials/opportunities and challenges for addressing CC. Research Methodology: This paper reviews the state of knowledge on the challenges of CC, particularly the challenges related to the large uncertainties in CC projections for parts of Africa, and opportunities in energy transition modeling and projections in Africa, which can be integrated with a relatively modest effort within a shift in Africa from an economic challenges view of CCs to a long-term perspective that emphasizes livelihood security and vulnerability reduction. This study reviews the literature to assess the challenges and opportunities of CC Africa. It also identifies policy recommendations. Results: The study found that to capitalize on the economic opportunities and bridge the economic challenges gap, governments in Africa, and technical and financial partners need to actively promote renewable energy and energy efficiency through investment incentives towards developing low-carbon economies. Conclusions: Climate change is a two-sided issue. It is a threat to our existence, but it also offers humanity a chance to get things right for future generations. Limitations: The study is limited to peer-reviewed research papers that cover part or the whole of Africa, concerned with the issue of the climate changes Contribution: The findings will be useful in informing African countries’ national and international processes concerned with the implementation of various international agreements on CC and the achievement of the 2030 Agenda on Sustainable Development.